2004
DOI: 10.1161/01.cir.0000146896.20317.59
|View full text |Cite
|
Sign up to set email alerts
|

Early Intertwin Differences in Myocardial Performance During the Twin-to-Twin Transfusion Syndrome

Abstract: Background-In the twin-to-twin transfusion syndrome (TTTS), pressure rather than volume overload is increasingly considered as a key factor in the pathogenesis of the cardiomyopathy of the recipient twin. If this is the case, cardiac dysfunction should be among the first signs observed with TTTS. The objective of this study was to determine whether intertwin differences in myocardial function are modified early in the course of TTTS and whether they can help to differentiate this condition from intrauterine gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 40 publications
9
94
0
1
Order By: Relevance
“…Although we have shown that the algorithm for staging the recipient's cardiomyopathy depicted in Figure 3 is not of prognostic value after laser coagulation, it outlines the importance of MPIs in the description of fetal cardiomyopathy along with their diagnostic value. Indeed, right and left ventricular performance indices were sufficient for an accurate classification of cardiac function across Profiles 1 to 3, confirming previous results addressing the value of cardiac function evaluation and particularly ventricular MPI as an early marker of TTTS in monochorionic twins 27,28 . This is further stressed by the lack of overlap between the cardiac profiles and the Quintero staging system, suggesting that at least part of the severity of the disease remains uncaptured by the latter 30 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although we have shown that the algorithm for staging the recipient's cardiomyopathy depicted in Figure 3 is not of prognostic value after laser coagulation, it outlines the importance of MPIs in the description of fetal cardiomyopathy along with their diagnostic value. Indeed, right and left ventricular performance indices were sufficient for an accurate classification of cardiac function across Profiles 1 to 3, confirming previous results addressing the value of cardiac function evaluation and particularly ventricular MPI as an early marker of TTTS in monochorionic twins 27,28 . This is further stressed by the lack of overlap between the cardiac profiles and the Quintero staging system, suggesting that at least part of the severity of the disease remains uncaptured by the latter 30 .…”
Section: Discussionsupporting
confidence: 86%
“…RV systolic function, diastolic function and MPI in both ventricles were impaired 21,22,27,28 . As reported in earlier studies 29 , UA-PI was raised in both donor and recipient twins, and DV abnormalities were more prevalent in the recipient than in the donor twin.…”
Section: Discussionmentioning
confidence: 96%
“…It can be used for early and differential diagnosis between twin-to-twin transfusion syndrome and intrauterine growth restriction because both have a similar initial presentation. Raboisson et al 13 found that the MPI increases in recipients twins because of a prolonged IVRT when compared with donor fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fetal hypertension in the recipients is also supported by characteristic glomerular and vascular renal histopathological changes, 9 as well as cardiomyopathy and cardiac dysfunction classical of increased afterload resulting from increased peripheral vascular resistance and high vascular pressure. 26 Studies of newborn BP report a constant and sustained rise in BP values over the first hours to days after birth, for all infants, preterm or term, singletons or (non TTTS-) twins, including twins with weight discordance. [13][14][15]23,27 In contrast, the current data show a decrease in BP during the first 12 h of life in recipients.…”
Section: Discussionmentioning
confidence: 99%